Pengaruh Lebar Kampuh Unfinish Terhadap Hasil Jadi Pada Batik Pekalongan - Pradana, Ferginanda Ayu (Jurnal Online Tata Busana, 2020)
ABSTRACT The definition of Unfinish is a way of embellishing fabric without using a finish, whereas to repair is to tear the fabric. Related to this research Batik fabric material from Pekalongan. In this study using Pekalongan batik because it has a dominant motif with flower and has a bright colour, usually indicated or caused by lines and dots. The purpose of this study are : 1) To determine the effect of unfinished results on Pekalongan batik with a width of 0,75 cm, 1 cm, and 1,25 cm, 2) To find out which results become the best unfinish using 0,75 cm, 1 cm, and 1,25 cm seam. In this study, including the type of research in which researchers use the method of observation to obtain data. While in this study the data analysis using a single ANOVA analysis with the help of SPSS 26. uses in this study related to the width of the unfinished seam on Pekalongan batik which find out about the stability of the form and the tidiness of the fuel. The aspect of shape stability in material with 1 cm seam width is better than 0.75 cm and 1.25 cm seam width, the aspect of the surface tidiness of material with 1 cm seam is better than 0.75 cm and 1.25 cm seam width . Then it can be concluded that unfinish seam with a width of 1 cm according to the results of all aspects used states the best value results. Keywords: Batik Pekalongan, Wide Kampuh, Unfinished.